A motivational systems approach to investigating opinions on climate change. (3rd July 2022) - Molden, Daniel C.; Bayes, Robin; Druckman, James N.
Abstract: Understanding how people form opinions about climate change has proven to be challenging. One of the most common approaches to studying climate change beliefs is to assume people employ motivated reasoning. We first detail how scholars in this area have applied motivated reasoning perspectives, identifying a variety of different judgment goals on which they have focused. We next argue that existing findings fail to conclusively show motivated reasoning, much less isolate which specific goals guide opinion formation about climate change. Then, we describe a novel motivational systems framework that would allow a more precise identification of the role of motivated reasoning in such opinions. Finally, we conclude by providing examples from completed and planned studies that apply this framework. Ultimately, we hope to give scholars and practitioners better tools to isolate why people hold the climate opinions they do and to develop effective communication strategies to change those opinions.